2017
DOI: 10.1016/j.bej.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Using in-situ viscosimetry and morphogranulometry to explore hydrolysis mechanisms of filter paper and pretreated sugarcane bagasse under semi-dilute suspensions

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. This is an author-deposited version published in : http://oatao.univ-toulouse.fr/ Eprints ID : 18375 a b s t r a c tThe relationship between in-situ viscosimetry, in-and ex-situ morphogranulometry, and biochemistry has been investigated during enzymatic hydrolysis of pretreated sugarcane bagasse (SCB, 3% w/v) and filter paper (FP, 1.5% w/v) at various enzyme dosages (0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
(57 reference statements)
0
5
0
1
Order By: Relevance
“…This study investigates the impact of cassava flour granulometry on the suspension viscosity and hydrolysis yield at low-temperature by a multiscale approach combining in-situ physical and ex-situ biochemical analyses. This multiscale approach has been previously applied to investigate the deconstruction of lignocellulosic-based biomass for biorefinery purposes [18][19][20] and feed additives in animal nutrition [21]. The first step was to characterize the initial viscosity and rheological behavior of suspensions as a function of concentration and granulometry.…”
Section: Introductionmentioning
confidence: 99%
“…This study investigates the impact of cassava flour granulometry on the suspension viscosity and hydrolysis yield at low-temperature by a multiscale approach combining in-situ physical and ex-situ biochemical analyses. This multiscale approach has been previously applied to investigate the deconstruction of lignocellulosic-based biomass for biorefinery purposes [18][19][20] and feed additives in animal nutrition [21]. The first step was to characterize the initial viscosity and rheological behavior of suspensions as a function of concentration and granulometry.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results on our system gave Np 0 = 0.17, α = 0.75, Kp = 115.2 and showed that a laminar regime prevailed up to Re = 41 (Nguyen et al, 2013; Le et al, 2017).…”
Section: Methodsmentioning
confidence: 70%
“…Pump P1 (archimede screw pump) is used to load progressively the reactor with the wheat bran substrate in order to generate a homogeneous suspension under permanent mixing. Pump P2 (volumetric peristaltic pump) is used to add quickly the enzymatic cocktail at a defined time (From Le et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While being a powerful tool for real-time analysis, in-rheometer monitoring of enzymatic liquefaction of fibrous lignocellulosic materials is inherently limited to the analysis of low-yield-stress/low-viscosity slurries as the mixing geometry must be able to promote continuous movement of the entire slurry without formation of a slip layer that would lead to sample fracture ( Stickel et al, 2009 ). In previous in-rheometer liquefaction studies ( Szijártó et al, 2011a , b ; Skovgaard et al, 2014 ; Le et al, 2017 ) relatively low solids loadings/low-viscosity slurries were therefore used, despite the fact that other studies have demonstrated that enzymatic hydrolysis kinetics differ substantially between low- and high-solids rheological regimes ( Knutsen and Liberatore, 2009 ; Modenbach and Nokes, 2013 ; Nguyen et al, 2015 ). Thus, we also examined whether the enzymatic liquefaction observed at low solids loadings, as measured via in-rheometer real-time monitoring in a semi-dilute regime, was representative of enzyme-mediated liquefaction in a concentrated (high solids loading) regime, where the slurry behaves as a structured fluid or soft solid.…”
Section: Discussionmentioning
confidence: 99%